2019
DOI: 10.1111/liv.14068
|View full text |Cite
|
Sign up to set email alerts
|

The concomitant loss of APC and HNF4α in adult hepatocytes does not contribute to hepatocarcinogenesis driven by β‐catenin activation

Abstract: Background & Aims Loss of hepatocyte nuclear factor‐4α (HNF4α), a critical factor driving liver development and differentiation, is frequently associated with hepatocellular carcinoma (HCC). Our recent data revealed that HNF4α level was decreased in mouse and human HCCs with activated β‐catenin signalling. In addition, increasing HNF4α level by miR‐34a inhibition slowed tumour progression of β‐catenin‐activated HCC in mice. Methods We generated a Hnf4aflox/flox/Apcflox/flox/TTR‐CreERT2 (Hnf4a/Apc∆Hep) mouse li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Consistently, we demonstrated that the increased OATP2B1 expression was induced by up-regulated HNF4α. Previous studies have reported that the increase of HNF4α expression is associated with HCC progression ( 44 , 45 ), and β-catenin signaling plays an important role in regulating HNF4α ( 46 ). Youmna Ali et al.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we demonstrated that the increased OATP2B1 expression was induced by up-regulated HNF4α. Previous studies have reported that the increase of HNF4α expression is associated with HCC progression ( 44 , 45 ), and β-catenin signaling plays an important role in regulating HNF4α ( 46 ). Youmna Ali et al.…”
Section: Discussionmentioning
confidence: 99%
“…The other patient had type 2 diabetes and showed obliterative portal venopathy and incomplete septal fibrosis. In patients with hepatocellular carcinoma (HCC), it is imperative to consider the possibility of a coexisting second potential trigger of HCC as PSVD is infrequently associated with HCC, 5 and the exact etiopathogenesis of HCC in the setting of PSVD is unclear. Also, incomplete septal cirrhosis may represent regressed cirrhosis and may be unrelated to the risk factors of PSVD.…”
mentioning
confidence: 99%